Agriculture - Zadeh, S.M.; Mateo-Sagasta, Javier; Antoniou, A.; Qadir, Manzoor; Chilton, J.; Carrion-Crespo, C.; Souza, M.de; Zandaryaa, S.; Medlicot, K. (2017)
This chapter reviews the main pollutants from agriculture, its associated impacts, and offers some key pollution mitigation options. The chapter also discusses how agriculture can be a beneficial user of wastewater, and how the practice can become safe.